Fatores biótico e abióticos que influenciam na concentração de podofilotoxina - Meira, Paloma Ribeiro (2013)
This paper describes the influence of abiotic and biotic factors in the concentration of secondary metabolites of pharmaceutical interest in medicinal plants, while it aims to answer how these factors influence the concentration of podophyllotoxin and yateína Leptohyptis macrostachys in vitro, this goal. The specimen Leptohyptis macrostachys was established in vitro from seeds collected in the Chapada Diamantina-Ba; studying the rate of germination rate, the germination and mean germination of seeds grown on MS medium with different concentrations of salts constituents of this medium as well as different concentrations of sucrose and gibberellic acid. Was also studied, such as abiotic factors (culture medium, carbon source temperature, photoperiod and gas exchange) and biological (plant growth regulators) influenced the development (number of shoots and leaves and roots presence of friable callus, compact or oxidized) and production of podophyllotoxin and yateína. To study the influence of these factors in getting these metabolites, plants were steeped at 40 ° C in ethanol to produce the extract. This was partitioned with water and after a specific treatment, injected into the HPLC. We established a protocol for Leptohyptis macrostachys growing from seeds in ½ MS medium supplemented with 1.5% sucrose and 11.55 mM of GA3, there was no significant formation of callus in treatments applied and the concentration of podophyllotoxin was favored when L. macrostachys was grown in ½ MS medium supplemented with 1.5% sucrose, closed with PVC film and kept in a growth room at 30 ° C.